O OLHAR DOS(AS) PROFESSORES(AS) DE GEOGRAFIA DA REDE ESTADUAL DE ENSINO EM AQUIDAUANA/MS: A IMPLANTAÇÃO DA BNCC E O NOVO ENSINO MÉDIO - INGRID MORAES LIMA (2024)
This dissertation aims to discuss the new educational reforms in force, specifically the National Common Curricular Base and the New Secondary Education, from the perspective of teachers of the Geography curricular component and the situation of their teaching work in the face of these reforms. The research focuses mainly on Geography teachers from the state education network of Aquidauana-MS who had experience working in the New High School (NEM) and who use the National Common Curricular Base (BNCC) to compose their lesson plans and, then, get to know the different perspectives of different subjects who are directly affected by these reforms. In general, our objective was to understand the teachers' perspective on the nuances of limiting autonomy regarding the implementation of the BNCC and the New Secondary Education in the state education network of Aquidauana–MS. To achieve the objectives, the Historical- Dialectical Method was used, since the current condition of Brazilian education was analyzed using observations based on the historical context that gave rise to its educational policies. From there, a bibliographical survey of works already produced on the subject was carried out, a documentary survey that governs Brazilian education, a qualitative analysis of the educational process and its context for a better understanding of its phenomena and their influence on teaching work and, finally, conducting and transcribing interviews with geography teachers. It can be concluded that the BNCC and the NEM are recent educational reforms that came from the top down and it is up to teachers to be constantly updated, as well as the devaluation of Human Sciences and consequently the loss of workload, in addition to an overload of content, which is why the feeling of devaluation and lack of prestige for these teachers is present.